Population decline in a ground-nesting solitary squash bee (Eucera pruinosa) following exposure to a neonicotinoid insecticide treated crop (Cucurbita pepo) - D. Susan Willis Chan (Nature Portfolio, 2021)
Abstract Insect pollinators are threatened by multiple environmental stressors, including pesticide exposure. Despite being important pollinators, solitary ground-nesting bees are inadequately represented by pesticide risk assessments reliant almost exclusively on honeybee ecotoxicology. Here we evaluate the effects of realistic exposure via squash crops treated with systemic insecticides (Admire-imidacloprid soil application, FarMore FI400-thiamethoxam seed-coating, or Coragen-chlorantraniliprole foliar spray) for a ground-nesting bee species (Hoary squash bee, Eucera pruinosa) in a 3-year semi-field experiment. Hoary squash bees provide essential pollination services to pumpkin and squash crops and commonly nest within cropping areas increasing their risk of pesticide exposure from soil, nectar, and pollen. When exposed to a crop treated at planting with soil-applied imidacloprid, these bees initiated 85% fewer nests, left 5.3 times more pollen unharvested, and produced 89% fewer offspring than untreated controls. No measurable impacts on bees from exposure to squash treated with thiamethoxam as a seed-coating or foliage sprayed with chlorantraniliprole were found. Our results demonstrate important sublethal effects of field-realistic exposure to a soil-applied neonicotinoid (imidacloprid) on bee behaviour and reproductive success. Soil must be considered a potential route of pesticide exposure in risk assessments, and restrictions on soil-applied insecticides may be justified, to mitigate impacts on ground-nesting solitary bee populations and the crop pollination services they provide.